Characterization of Salivary Secreted Proteins That Induce Cell Death From Riptortus pedestris (Fabricius) and Their Roles in Insect-Plant Interactions - Dong, Yumei; Huang, Xingge; Yang, Yuxia; Li, Jifen; Zhang, Meiqian; Shen, Hui; Ren, Yanrong; Li, Xinyu; Tian, Jiale; Shen, Danyu; Dou, Daolong; Xia, Ai (Frontiers in Plant Science, 2022)
Riptortus pedestris (Fabricius) is a polyphagous hemipteran crop pest that mainly feeds on the leguminous plants, resulting in shriveled and dimpled seeds. With recent several outbreaks in the Huang-Huai-Hai region of China, as well as in South Korea and Japan, this species has caused enormous economic losses to soybean crops. In the present study, we found that R. pedestris feeding results in local lesions at the infestation sites. To identify the key effectors that induce plant damage during feeding, the salivary glands of R. pedestris were dissected for transcriptome sequencing, and 200 putative secreted proteins were transiently expressed in N. benthamiana. Among them, three intracellular effectors (RP191, RP246, and RP302) and one apoplastic effector (RP309) were identified as necrosis-inducing proteins (NIPs), which also triggered the reactive oxidative burst. Yeast signal sequence trap and qRT-PCR analysis suggested that these proteins might be secreted into plant tissue during R. pedestris infestation. Pathogenicity assays revealed that RP191, 246, and 302 promote Phytophthora capsici infection or induce Spodoptera litura feeding by inhibiting plant immunity. RP302 is localized to the cytoplasm and nuclei, while RP191 and 246 are endoplasmic reticulum (ER) resident proteins. RP309 stimulates the expression of PTI marker genes, and its induced cell death depends on co-receptors NbBAK1 and NbSOBIR1, indicating that it is a HAMP. Bioinformatics analysis demonstrated that four NIPs are recently evolved effectors and only conserved in the Pentatomidae. In this study, saliva-secreted proteins were used as the starting point to preliminarily analyze the harm mechanism of R. pedestris, which might provide a new idea and theoretical basis for this species control.